Combined Effects of Particulate Matter Exposure and Exercise Training on Neuroplasticity-Related Growth Factors and Blood–Brain Barrier Integrity - Su-Youn Cho; Hee-Tae Roh (Atmosphere, 2025)
Particulate matter (PM) negatively impacts brain health, while exercise training can mitigate these effects and promote brain health. However, the effect of the interaction between PM exposure and exercise on brain health remains insufficiently explored. This study investigated the effects of PM exposure and exercise training on neuroplasticity-related growth factors and blood–brain barrier (BBB) integrity. Forty male C57BL/6 mice were randomly assigned to four groups as follows: control (CON, n = 10), PM exposure (PM, n = 10), exercise training (EX, n = 10), and PM exposure with exercise training (PMEX, n = 10). PM exposure and exercise training interventions were conducted over 8 weeks. The PM group showed significantly elevated levels of malondialdehyde (MDA), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), S100 calcium-binding protein β (S100β), and neuron-specific enolase (NSE) (p < 0.05) and reduced levels of superoxide dismutase (SOD), insulin-like growth factor-1 (IGF-1), brain-derived neurotrophic factor (BDNF), and vascular endothelial growth factor (VEGF) (p < 0.05) compared to the CON and EX groups. Conversely, the EX group demonstrated significantly reduced MDA, IL-6, TNF-α, S100β, and NSE levels (p < 0.05) and enhanced SOD, IGF-1, BDNF, and VEGF levels (p < 0.05) compared to the PM group. However, the PMEX group exhibited attenuated benefits, showing higher MDA, IL-6, TNF-α, S100β, and NSE levels (p < 0.05) and lower SOD and IGF-1 levels (p < 0.05) compared to the EX group. These findings suggest that PM exposure induces oxidative stress, inflammation, and BBB disruption while downregulating neuroplasticity-related growth factors. Exercise training mitigates these adverse effects by enhancing antioxidant activity, reducing inflammation, upregulating neuroplasticity-related growth factors, and preserving BBB integrity. However, the protective effects of exercise may be partially diminished under conditions of PM exposure.